2020
DOI: 10.21272/jes.2020.7(1).f5
|View full text |Cite
|
Sign up to set email alerts
|

Intensification of Paper Drying on Drying Cylinders

Abstract: One of the most energy-intensive processes is the drying process. Therefore, an important task is to reduce heat consumption for drying. Various ways to improve the drying devices of paper and cardboard machines are identified. The main disadvantages of these improvements are given. The limiting factor of heat transfer from water vapor to paper is established. The dependence of thermal resistance on the thickness of the condensate layer is given. The authors have developed a new design for condensate drainage.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Yankee cylinder studies in 2013 showed that one of the problems with its low energy efficiency was internal condensate water in the cylinder [40]. In order to improve the operation of the drying section, in 2014 the share of the Yankee cylinder in the drying process was increased.…”
Section: Heat Energy Consumption Per Ton Of Produced Papermentioning
confidence: 99%
“…Yankee cylinder studies in 2013 showed that one of the problems with its low energy efficiency was internal condensate water in the cylinder [40]. In order to improve the operation of the drying section, in 2014 the share of the Yankee cylinder in the drying process was increased.…”
Section: Heat Energy Consumption Per Ton Of Produced Papermentioning
confidence: 99%